Flow irregularities from syringe infusion pumps caused by syringe stiction. Issue 8 (25th June 2020) - Peduzzi, Neris; Batliner, Martin; Grass, Beate; Buehler, Philipp K.; Schmid Daners, Marianne; Meboldt, Mirko; Weiss, Markus
Abstract: Objective: The current study aimed to evaluate the extent of the slide‐stick phenomenon in differently designed infusion syringes at various infusion rates and filling positions. Methods: Fluid delivery from three 50‐mL infusion syringe brands (BD; Codan; Fresenius) was investigated using a flow sensor at flow rates of 0.5, 1.0, or 5.0 mL h −1, with the syringes filled with either 10, 30, or 50 mL of distilled water. Two identical models (A/B) of the same infusion pump model were used. The effect of flow rate variations on the plasma concentration of a continuous epinephrine infusion in a 3 kg neonate receiving a continuous infusion of 0.1 μg kg min −1 epinephrine was studied using a pharmacokinetic simulation model. Results: Considerable variations in calculated plasma epinephrine concentration were detected between flow rates of 5 and 0.5 or 1 mL h −1 for all syringe types and filling volumes. The median deviation of plasma concentration for the 5 mL h −1 flow rate varied depending on assembly from 1.3% (Codan) to 1.8% (Fresenius). This was more pronounced for lower flow rates, where at 1 mL h −1 the deviation varied from 3.3% (BD) to 4.8% (Fresenius) and at 0.5 mL h −1 from 4.9% (BD) to 5.4% (Fresenius). Differences between filling volumes (within syringe type and flow rate) did not appear to have relevant influence on variations in calculated plasma epinephrine concentration. Conclusion: Infusion set rate rather than syringe brand or filling volume was a major predictor for syringe stiction‐related amount of variation in the calculated plasma epinephrine concentration.